2017
DOI: 10.1177/0003319717710114
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Outcomes After In Situ Reconstructions for Aortic Graft Infection

Abstract: In situ reconstruction may be considered as first-line treatment. Our results suggest that silver polyesters appear to be most appropriate for older patients, and in order to limit reinfection, autogenous veins are probably the most suitable conduit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 64 publications
3
65
1
1
Order By: Relevance
“…14e17 In a recent meta-analysis, the risk of re-infection has been studied according to different infecting micro-organisms. 17 Staphylococcus aureus, Enterobacteriaceae, Pseudomonas aeruginosa, and beta haemolytic streptococci were classified as virulent, while bacteria belonging to the skin colonising flora such as Staphylococcus epidermidis, corynebacterial, and Cutibacterium acnes were classified as non-virulent agents. The results of this meta-analysis established that virulent organisms were significantly associated with an increased risk of re-infection.…”
Section: Szilagyi Classificationmentioning
confidence: 99%
See 4 more Smart Citations
“…14e17 In a recent meta-analysis, the risk of re-infection has been studied according to different infecting micro-organisms. 17 Staphylococcus aureus, Enterobacteriaceae, Pseudomonas aeruginosa, and beta haemolytic streptococci were classified as virulent, while bacteria belonging to the skin colonising flora such as Staphylococcus epidermidis, corynebacterial, and Cutibacterium acnes were classified as non-virulent agents. The results of this meta-analysis established that virulent organisms were significantly associated with an increased risk of re-infection.…”
Section: Szilagyi Classificationmentioning
confidence: 99%
“…Low amputation rates and high patency rates are reported (Table 10). 17,163 There is no comparison between different silver coatings. Only one study (n ¼ 10 patients) has reported the effect of elemental silver graft for ISR in the aorto-iliac position, and describing one re-infection.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 3 more Smart Citations